The effects of long term weed management on the abundance and diversity of noqious monocot weed speices in a banana plantation and paraquat resistance of cynodon dactylon - Jamaluddin, Sheara-Jane Looc. (2011)
Banana plantations are going into slopes, and weed management in these areas need to strike a balance between reducing weed populations and preventing soil erosion. A four-year study was conducted to compare manual and chemical weed management in two slopes: 15% and 25%. Counts and biomass in the field and seedling emergence in the seed banks of seven monocot weed species were monitored. There was no significant difference in the weed field counts and biomass of manual and chemical plots. Chemical treatment was more effective in controlling some species, such as Eleusine indica and Paspalum conjugatum. Based on weed seedling emergence in the seed banks, the counts were not significantly reduced and weed population was not significantly higher in manual plots than in chemical plots. Trends and exceptions in the field counts were explained in terms of the biological characteristics of weed species and their differential response to weed control treatments. Species diversity was significantly higher in chemical plots because of minimal disturbance that makes the soil intact. Greenhouse experiment was conducted to determine if paraquat resistance exists in Cynodon dactylon. C. dactylon seedlings were sprayed with different doses of paraquat. There was a significant decrease in the percent survival between plants from two seeds sources and frequency of paraquat resistant plants. Meanwhile, resistant individuals delay maturation and decrease number of seeds as the stress from paraquat increases. The experiments led to the following conclusions: 1) reduction in total weed population did not differ between manual and chemical weed management, but chemical weed management resulted in statistically higher weed species diversity; 2) C. dactylon, either from the wild or from the field exposed to paraquat, is resistant to paraquat
Thesis (BS Biology) -- University of the Philippines Mindanao, 2011
Keywords: Banana plantation; Slope farming; Weed management; Paraquat resistance; Weed population; Weeds; Chemical weeding; Paspalum conjugatum; Eleusine indica; Chemical treatment; Manual plots; Chemical plots; Herbicides; Bermuda grass